(Incumbent) politics and burdens in the social construction of target groups: The Brazilian Bolsa Família conditional cash transfer programme. (20th April 2017) - Silvestre, Hugo Consciência
Abstract: This study is a contribution to the study of the social construction of target groups framework (SCTG). Applying a case study model, it is argued that politicians are promoting a policy design that itself affects politics. This conclusion is based on the Brazilian Bolsa Família conditional cash transfer programme, in which beneficiaries own the political resources (voting) to choose their representatives. Therefore, beneficiaries can influence policy designs in their favour. Also, the political gains that have been accomplished are shifting the tax burdens to other classes, which can change beneficiaries' social construction. Altogether, two propositions from the SCTG need further discussion: the degree of burden on other social groups and (incumbent) politics.